Training load and recovery in elite synchronized swimming - Schaal, K.; Le Meur, Y.; Hausswirth, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Elite synchronized swimming is an aesthetic and highly technical judged sport evolving quickly. The emphasis on technical perfection within increasingly difficult and physically demanding routines requires a very high level of fitness and precision, attained through numerous hours of daily training. In order to follow such rigorous training while avoiding excess fatigue accumulation, integrating adequate recovery quality and quantity into the athletes` training plan is key. We present a summary of the physical demands and recovery needs of elite synchronized swimmers, with an emphasis on both acute and chronic recovery. Execution of a single competition routine requires maximal aerobic work production with large anaerobic contributions. Hence, in the context of repeated performances separated by a short time period (1 hr), as can be the case during competition, acute recovery strategies should be aimed at improving blood lactate clearance and reducing muscle fatigue to enable repeated maximal work production. We demonstrated that active recovery and whole body cryotherapy (WBC) were similarly effective in this regard, while WBC also afforded a large cardiac parasympathetic reactivation within 1 hour after performance (1). Parasympathetic reactivation may improve the quality of passive recovery after intense training sessions and promote better sleep quality (2). In a context of intensified training (IT) periods, particular attention must be paid to the quality of day-to-day passive recovery, in order to help avoid excess fatigue accumulation. We recently described the daily recovery quality of these swimmers and its degradation during IT periods, as they show impaired sleep quality and reduced sleep quantity, while failing to increase caloric intake sufficiently to meet sharply increased energy needs. Increased sleep disturbance, fatigue, and changes in autonomic function hinted at the onset of an overreached state (3, 4), while changes in the swimmers` endocrine profile pointed to a state of energy conservation during this important pre-competition period. Integrating daily WBC sessions during IT, however, helped reduce some of the adverse effects of IT on sleep, fatigue, autonomic function, and exercise performance, but did not influence food intake. Greater emphasis must be placed on identifying the nutritional and sleep needs of elite synchronized swimmers, in order to program adequate recovery strategies that will help them train effectively to maximize performance gains.